Development of web based learning content of animation algorithm on searching and sorting techniques / Nur Linda Abdi Nur - Abdi Nur, Nur Linda (2007)
Web based learning environment has been widely developed and adopted. Many of us use the internet or the "web" (World Wide Web) as a source of information. It is not easy to study searching and sorting algorithm with only refers to the text algorithm like in text books. This project is to develop a web based on searching and sorting techniques to improve the quality of study among the student in FTMSK UiTM. In sorting algorithm, we focused on quick sort, heap sort, merge sort, bubble sort, insertion sort and selection sort while in searching algorithm we focused on binary search and sequential search. The objectives of this project is to develop self-learning environment in learning searching and sorting algorithm, enhance understanding of student in learning searching and sorting technique and to apply web-based learning in computer science subject, which focus on courses that use searching and sorting algorithm.